Implementasi Zakat Produktif Dan Konsumtif Dalam Meningkatkan Kesejahteraan Ekonomi Mustahik : Studi Kasus Baznas Sidrap SULSEL - Umar, Umar; Luthfi, Mukhtar; Ambo, Rahman (Tasamuh: Jurnal Studi Islam, 2023)
This paper aims to describe the implementation of productive and consumptive zakat in improving the economic welfare of mustahik in Baznas Sidrap South Sulawesi in terms of distribution patterns, program effectiveness, and supporters and obstacles. This type of research is descriptive qualitative with observation, interview, and documentation methods. Furthermore, the data obtained will be analyzed through syar'i and juridical approaches. The results of this study show that: 1) The pattern of zakat distribution in Baznas Sidrap uses two patterns, namely productive and consumptive distribution. 2) Baznas Sidrap programs, namely: first, Sidrap Cares, namely basic food assistance, house assistance worth 50 million, mass circumcision, funeral benefits, victims of natural disasters, house renovations, and distribution of aid to Muallaf. Second, Sidrap Cerdas is assistance for completing studies, mosque councils, funds to Al-Azhar Cairo, and honorary funds. Third, Sidrap Mandiri is business capital assistance and tools for business. Fourth, Sidrap Sehat is medical funding assistance and clinic creation. Fifth, Religious Sidrap is assistance for zakat and waqf counseling activities, religious competitions, santri days, and STQH activity funds. 3) Supporters of productive and consumptive zakat are the many potentials of zakat and are supported by the government. The obstacles are that public understanding of zakat is still lacking, lack of public trust in Baznas, locations that are difficult to reach, and zakat funds are still low.